Enhancing Stock Market Return with New Product Preannouncements: The Role of Information Quality and Innovativeness. Issue 4 (19th August 2015) - Lee, Ruby P.; Chen, Qimei; Hartmann, Nathaniel N.
Abstract : To advance development and application of signaling theory in the new product preannouncement literature while seeking to resolve ambiguity regarding the influence of innovativeness on stock market return, the role of information quality is examined. Specifically, this study investigates the effect of innovativeness across low and high levels of information quality. The results, ascertained using event study methodology on a sample of 243 new product preannouncements collected over a nine‐year period, indicate that higher information quality increases the strength of the positive relationship between innovativeness and stock market return. The findings offer managers insight into what role information quality plays in new product preannouncements that can help their firms generate higher stock market return.